2022
DOI: 10.1177/00033197221091317
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis and Non-Alcoholic Fatty Liver Disease

Abstract: Non-alcoholic fatty liver disease (NAFLD) is a common disease defined by excess fat deposition in the liver. The course of NAFLD is not fully understood, however, some pathogenic mechanisms have been identified. Accumulation of fat in liver cells is associated with insulin resistance, central obesity, triglyceride accumulation in the liver and hepatic fatty acid metabolism dysregulation that cause steatosis. The other process leads to hepatocyte inflammation and necrosis, which leads to severe hepatic disease;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 113 publications
0
4
0
Order By: Relevance
“…Additionally, studies showed Genistein treats NAFLD by targeting Thromboxane A2. Our findings regarding its effect on the expression regulation of genes related to Apoptosis ( NOS3 ), Thrombogertesis inflammation atherosclerosis 74 ( ICAM1 56 ), and Mesangial matrix expansion ( FN1 ) may suggest new drug treatment mechanisms for NAFLD ( Fig. S3 C ).…”
Section: Discussionmentioning
confidence: 84%
“…Additionally, studies showed Genistein treats NAFLD by targeting Thromboxane A2. Our findings regarding its effect on the expression regulation of genes related to Apoptosis ( NOS3 ), Thrombogertesis inflammation atherosclerosis 74 ( ICAM1 56 ), and Mesangial matrix expansion ( FN1 ) may suggest new drug treatment mechanisms for NAFLD ( Fig. S3 C ).…”
Section: Discussionmentioning
confidence: 84%
“…The presence of a hypercoagulable state in patients with MASLD has the potential to result in the formation of microthrombi in the hepatic veins and arteries, leading to disrupted blood flow [58]. Increased rates of clinically significant thrombotic events, such as pulmonary embolism, deep vein thrombosis, and portal vein thrombosis, are explicable by abnormalities at all stages of hemostasis [83,84], including a condition of hypercoagulation derived from decreased levels of PAI-1 [61,72,73].…”
Section: Coagulation Dysfunctionsmentioning
confidence: 99%
“…The clinical presentations of atherosclerotic disease encompass coronary artery disease, peripheral arterial disease, and stroke. Atherosclerosis (AS) is a dynamic and progressive condition that results from the convergence of aberrant lipid metabolism, endothelial dysfunction, and inflammation [83,84,105,193]. An essential stage in the inflammatory process involves the penetration of monocytes into the subendothelial region of major arteries and their subsequent transformation into tissue macrophages.…”
Section: Adiponectinmentioning
confidence: 99%
“…The underlying mechanisms that link MAFLD to an increased risk of CVD primarily involve heightened inflammation, insulin resistance, oxidative stress, and perturbations in hepatic metabolites ( 8 , 9 ). Specifically, MAFLD has garnered substantial attention for its role in promoting systemic inflammation through hepatic steatosis-secreted inflammatory proteins such as interleukin-6, C-reactive protein, fibrinogen, monocyte chemoattractant protein-1, and tumor necrosis factor-alpha ( 10 ). These inflammatory proteins augment the uptake of plasma-derived lipoproteins by macrophages, forming foam cells laden with lipids and initiating the development of atherosclerotic lesions by activating the adaptive immune system ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%